Numerical Evaluation of Conformal Mapping and its Inverse for Unbounded Multiply Connected Regions - Yunus, AAM; Murid, AHM; Nasser, MMS (Malaysian Mathematical Sciences Soc, 2024)
Indexed by SCOPUS/WOS